Local labor market effects of FDI regulation in Indonesia - Robert Genthner; Krisztina Kis-Katos (ZBW - Leibniz Information Centre for Economics, 2020)
Using yearly Indonesian labor market data for 2000 to 2015, we investigate the impact of a protectionist foreign direct investment (FDI) policy reform on employment and wages. The so-called negative investment list regulates FDI at the highly granular product level and has been repeatedly revised throughout time. We construct spatial measures of regulatory penetration based on firm-level data and thereby exploit the exposure of local manufacturing industry employment to the negative investment list. Controlling for time and locality fixed effects as well as trends in initial district conditions, our findings suggest an overall positive effect of local regulatory penetration on employment, which is especially pronounced among young, females and low-skilled workers and mostly driven by job creation in the manufacturing sector. We also present evidence in support of positive wage effects.
Keywords: F16; F21; F23; J23; J31; L51; 330; FDI regulation; Indonesia; local labor markets